Cote d'Ivoire : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Poverty Reduction Strategy Paper (PRSP) for Cote d'Ivoire. The paper reveals that poverty is more acute in rural areas than in urban areas of Cote d'Ivoire. The increase of poverty is greater in the city of Abidjan, with about a 50 percent increase, compared with other towns where the rate of increase is slightly below 20 percent. As at the national level, poverty increased considerably at the level of development poles (regions) and differed from one pole to the other.